METHODOLOGICAL SUBSTANTIATION OF THE “SCIENCE OF NATURE” IN THE WORKS BY ANANIA SHIRAKATSI - MIRUMYAN, KARLEN (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
The article presents the methodological conception of the Armenian scientist and philosopher of the 7th century Anania Shirakatsi on the correlation of ancient scientific and philosophical legacy and Christian teachings, philosophy, and theology, reason, and faith, which was pivotal for the early Middle Ages. The article shows that the scientist discerns a certain connection and continuity between pagan teachings and the Christian worldview. If the object of the study of pagan science is the cosmos as a whole, then the object of the study of Christian thinkers is the achievements of pagan science. Therefore, the result of the cognitive activity of pagan philosophers has become the subject of study and a means of cognition for Christian authors. The article considers the system of arguments of Anania Shirakatsi, substantiating the principle of consistency of ancient science and Christian teachings.